ANALISIS KENYAMANAN SPASIAL DAN FASILITAS LANSKAP PADA KAWASAN WATERFRONT BENTENG KUTO BESAK PALEMBANG (Jurnal Arsitektur ARCADE, 2026)
Traditional architecture as a tangible cultural heritage asset requires dynamic preservation efforts through protection, development, and utilization to maintain its existence and enhance its value for future generations. The identity of Palembang as a Water City, recognized since the era of the Palembang Darussalam Sultanate, is reflected in the presence of the Musi River and Benteng Kuto Besak as significant historical and cultural elements. However, the Waterfront area of Benteng Kuto Besak and its surroundings has not been optimally managed as a historic district and as part of Palembang’s urban development. In fact, the Musi River waterfront holds substantial potential in economic, cultural, historical, and sustainable tourism aspects. This study aims to analyze the role of the Musi River waterfront around Benteng Kuto Besak in enhancing sustainable tourism in Palembang through a heritage preservation approach and the strengthening of city identity. In addition, structural considerations are addressed through the use of steel sheet pile foundations with a diameter of 500 mm and a length of 22 m, designed based on allowable stress and loading factors, including seismic forces, to ensure safety and long-term sustainability of the riverside area.